Nilai Pendidikan Karakter dan Kearifan Lokal dalam Cerita Rakyat Banyumas serta Implementasinya terhadap Pembelajaran Bahasa Indonesia - Nurlaili, Fadilla Intan; Sukirno (UM Purwokerto Press, 2024)
This research aims to examine the values of character education and local wisdom contained in Banyumas folklore and its implementation in Indonesian language teaching in high schools. Folktales such as